2013
DOI: 10.4236/ajps.2013.43078
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Adaptation of <i>Adenophora triphylla var. japonica</i> (Campanulaceae)

Abstract: The comparative morphology and anatomy of leaves between the coastal ecotype and the normal type of Adenophora triphylla (Thunb.) A.DC. var. japonica (Regel) H.Hara (Campanulaceae) were examined to clarify the differences in morphological characters between the 2 groups. Morphological and anatomical analyses revealed that the coastal ecotype had a thicker leaf than the normal type, because of the increased size of epidermal and spongy cells. Thus, the main morphological change from the normal type into the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the present study, we found that coastal E. japonica has significantly smaller stomata and larger epidermal cells than inland area species, indicating that the former gained adaptive characteristics in coastal areas. Many studies have reported that coastal adaptation included a decrease in stomatal density (Tunala et al, 2012;Ohga et al, 2013;Kumekawa et al, 2013). Contrastingly, Takizawa et al (2022) reported that woody Ligustrum japonicum had significantly smaller stomatal sizes in coastal areas than those in inland area species and hypothesized that woody plants could not invade coastal areas from inland areas without stomatal changes, although woody plants could adapt to coastal areas by reducing stomatal size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we found that coastal E. japonica has significantly smaller stomata and larger epidermal cells than inland area species, indicating that the former gained adaptive characteristics in coastal areas. Many studies have reported that coastal adaptation included a decrease in stomatal density (Tunala et al, 2012;Ohga et al, 2013;Kumekawa et al, 2013). Contrastingly, Takizawa et al (2022) reported that woody Ligustrum japonicum had significantly smaller stomatal sizes in coastal areas than those in inland area species and hypothesized that woody plants could not invade coastal areas from inland areas without stomatal changes, although woody plants could adapt to coastal areas by reducing stomatal size.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal plants are known for their rich biodiversity and high level of endemism, including a concentration of rare and threatened taxa and high diversity of endemic plant species (Burgess et al, 1998;Lovett, 1998;Myers et al, 2000;Azeria et al, 2007), and they have implications for biodiversity conservation (van der Meulen & Udo de Haes, 1996;Cori, 1999;Schlacher et al, 2008). Particular attention has been focused on understanding ecophysiological mechanisms involved at the cellular and molecular levels (Elhaak et al, 1997;Migahid & Elhaak, 2001;Tunala et al, 2012;Kumekawa et al, 2013;Ohga et al, 2013;Sunami et al, 2013;Takizawa et al, 2022). It is uncertain whether plant species widely distributed from inland to coastal areas have adapted with or without morphological changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thicker leaves are caused by increased leaf water content and subsequent accumulation of large amounts of solute without an increase in the osmotic pressure of cells (Suá rez & Sobrado, 2000). Consequently, species with thicker leaves can be found in drought-prone environments (Ohga et al, 2013;Tunala et al, 2012). The edaphic characteristics of serpentine were important in many cases, such as metal toxicity, an adverse Ca/Mg quotient, and drought (Kruckeberg, 1951(Kruckeberg, , 1954.…”
Section: Discussionmentioning
confidence: 99%
“…The biodiversity of coastal environments is valuable at the global scale, as these environments have high endemism rates of plant species that occur as a result of the unique environments, with strong persistence of shore winds carrying sand and salt spray that dries leaves and soil (Hassani et al, 2021;Nakajima & Yoshizaki, 2018). Plant species in coastal areas have traits adapted to coastal environments (Kumekawa et al, 2013;Ohga et al, 2013;Shiba et al, 2022;Sunami et al, 2013;Takizawa et al, 2022;Tunala et al, 2012); therefore, the conservation and sustainable use of coastal forests require close attention (Cori, 1999;Schlacher et al, 2008).…”
Section: Introductionmentioning
confidence: 99%